Regulation of angiotensinogen by angiotensin II in mouse primary astrocyte cultures - O’Callaghan, E. L.; Bassi, J. K.; Porrello, E. R.; Delbridge, L. M. D.; Thomas, W. G.; Allen, A. M. (Journal of neurochemistry, 2011)
J. Neurochem. (2011) 119, 18–26. Astrocytes are the major source of angiotensinogen in the brain and play an important role in the brain renin‐angiotensin system. Regulating brain angiotensinogen production alters blood pressure and fluid and electrolyte homeostasis. In turn, several physiological and pathological manipulations alter expression of angiotensinogen in brain. Surprisingly, little is known about the factors that regulate astrocytic expression of angiotensinogen. There is evidence that angiotensinogen production in both hepatocytes and cardiac myocytes can be positively regulated via the angiotensin type 1 receptor, but this effect has not yet been studied in astrocytes. Therefore, the aim of this project was to establish whether angiotensin II modulates angiotensinogen production in brain astrocytes. Primary astrocyte cultures, prepared from neonatal C57Bl6 mice, expressed angiotensinogen measured by immunocytochemistry and real‐time PCR. Using a variety of approaches we were unable to identify angiotensin receptors on cultured astrocytes. Exposure of cultured astrocytes to angiotensin II also did not affect angiotensinogen expression. When astrocyte cultures were transduced with the angiotensin type 1A receptor, using adenoviral vectors, angiotensin II induced a robust down‐regulation (91.4% ± 1.8%, p < 0.01, n = 4) of angiotensinogen gene expression. We conclude that receptors for angiotensin II are present in extremely low levels in astrocytes, and that this concurs with available data in vivo. The signaling pathways activated by the angiotensin type 1A receptor are negatively coupled to angiotensinogen expression and represent a powerful pathway for decreasing expression of this protein, potentially via signaling pathways coupled to Gαq/11.